Links with 4 components and 10 crossings

This table includes the knot designation, followed by the braid representation used by the braid programme, followed by the Alexander polynomial.

Output from braid v5.0.b1



-- L(4)10(1)-a
-s1-s2s3s3s3s3-s2s1-s2s3s3-s2
Alexander polynomial = t^7-5t^6+10t^5-12t^4+12t^3-10t^2+5t-1

-- L(4)10(1)-b
-s1s2s2s2s2-s1-s3s2s2-s3
Alexander polynomial = t^7-5t^6+10t^5-12t^4+12t^3-10t^2+5t-1

-- L(4)10(1)-c
-s1s2s2s3s2s2s1s2s2-s3s2s2s2s2
Alexander polynomial = 2t^7-6t^6+9t^5-11t^4+11t^3-9t^2+6t-2

-- L(4)10(1)-d
s1-s2s3s3-s2-s1-s2s3s3s3s3-s2
Alexander polynomial = t^7-5t^6+10t^5-12t^4+12t^3-10t^2+5t-1

-- L(4)10(1)-e
-s1-s2s3s3-s2s1-s4s3s3s2-s3s4-s3-s2-s4
Alexander polynomial = -2t^5+9t^4-17t^3+17t^2-9t+2

-- L(4)10(1)-f
s1-s2s3s3s4-s3s2-s3-s2-s1-s2-s4s3s3-s2
Alexander polynomial = -2t^5+9t^4-17t^3+17t^2-9t+2

-- L(4)10(1)-g
s1-s2s3s3-s2-s1s4-s3s2-s3-s2-s4s3s3-s2
Alexander polynomial = -2t^5+9t^4-17t^3+17t^2-9t+2

-- L(4)10(1)-h
s1s2-s3s4s5-s4-s4-s3-s2-s1-s3-s2-s3s4-s3s2-s3-s5-s4-s4
Alexander polynomial = -7t^3+21t^2-21t+7

-- L(4)10(2)-a
-s1-s2s3-s4s3s2s1s4-s3s2-s3s4s4-s3-s2-s3s4
Alexander polynomial = -2t^5+11t^4-23t^3+23t^2-11t+2

-- L(4)10(2)-b
-s1s2-s3s2s1s3-s2-s4s3s3-s2-s4s3
Alexander polynomial = -2t^5+11t^4-23t^3+23t^2-11t+2

-- L(4)10(2)-c
-s1s2s2s3s3s4s3s2s2s1s2s2-s3s2-s4-s3s2
Alexander polynomial = -4t^5+13t^4-19t^3+19t^2-13t+4

-- L(4)10(2)-d
s1s2-s3s4s4-s3-s2-s1-s3s2s3-s4s3-s2s4s4-s3
Alexander polynomial = -2t^5+11t^4-23t^3+23t^2-11t+2

-- L(4)10(2)-e
-s1s2s2-s1-s3-s3-s3s2s2-s3
Alexander polynomial = t^7-5t^6+12t^5-18t^4+18t^3-12t^2+5t-1

-- L(4)10(2)-f
s1-s2s3s3-s2-s1-s2-s2-s2s3s3-s2
Alexander polynomial = t^7-5t^6+12t^5-18t^4+18t^3-12t^2+5t-1

-- L(4)10(2)-g
s1-s2s3s3-s2-s2-s2-s1-s2s3s3-s2
Alexander polynomial = t^7-5t^6+12t^5-18t^4+18t^3-12t^2+5t-1

-- L(4)10(2)-h
s1s2-s3-s4-s4-s4-s4-s3-s2-s1-s3-s2-s3s4-s3s2-s3
Alexander polynomial = 4t^5-13t^4+19t^3-19t^2+13t-4

-- L(4)10(3)-a
-s1-s2-s3s4s4s3-s2s1-s2s3s3-s2s4
Alexander polynomial = -2t^5+10t^4-20t^3+20t^2-10t+2

-- L(4)10(3)-b
s1s2-s3s2s2-s1s3-s2-s4s3s3-s2-s4
Alexander polynomial = -2t^5+10t^4-20t^3+20t^2-10t+2

-- L(4)10(3)-c
-s1s2s2-s3s2s2s1-s2s3s3s2s2s2s3
Alexander polynomial = 3t^5-11t^4+18t^3-18t^2+11t-3

-- L(4)10(3)-d
s1s2-s3s4s4-s3-s2-s1-s3s2s3-s4s3s3-s2s4-s3
Alexander polynomial = -2t^5+10t^4-20t^3+20t^2-10t+2

-- L(4)10(3)-e
-s1s2s2-s1s3-s4s3s3s2-s4-s3
Alexander polynomial = -2t^5+10t^4-20t^3+20t^2-10t+2

-- L(4)10(3)-f
s1-s2s3s3-s2-s1-s2s4-s3s4s4-s3s2s3-s4
Alexander polynomial = -2t^5+10t^4-20t^3+20t^2-10t+2

-- L(4)10(3)-g
s1s2s3-s4s3s3-s2-s1s4-s3-s2-s3s4s4-s3s2-s3
Alexander polynomial = -2t^5+10t^4-20t^3+20t^2-10t+2

-- L(4)10(3)-h
s1s2s3-s4s5-s4-s3-s2-s1-s4-s3-s2-s4-s3-s4s5-s4s3s2-s4s3-s4
Alexander polynomial = t^5-9t^4+22t^3-22t^2+9t-1

-- L(4)10(4)  (2,2,2)(2,2)-a
-s1-s2s3-s4s3s2s1s3s2s3s3s4s4s3s3-s2s3
Alexander polynomial = -4t^5+14t^4-22t^3+22t^2-14t+4

-- L(4)10(4)  (2,2,2)(23-b
s1-s2s3s4s3s5s4s3-s2-s1-s2s3-s4s3-s5-s4s3-s2
Alexander polynomial = t^5-11t^4+28t^3-28t^2+11t-1

-- L(4)10(4)  (2,2,2)(22-c
-s1s2-s3-s3s2s1s2s2-s3-s3s2s2
Alexander polynomial = -t^7+5t^6-13t^5+21t^4-21t^3+13t^2-5t+1

-- L(4)10(4)  (2,2,2)(22-d
-s1s2-s3-s3s2s1-s2-s2-s3-s3-s4-s3s2-s3s4
Alexander polynomial = -3t^5+13t^4-24t^3+24t^2-13t+3

-- L(4)10(4)  (2,2,2)(24-e
-s1s2s2-s3-s3s2s2s1s2-s3-s3s2
Alexander polynomial = -t^7+5t^6-13t^5+21t^4-21t^3+13t^2-5t+1

-- L(4)10(4)  (2,2,2)(22-f
s1-s2-s3-s3-s2-s1-s2-s2s3-s4s3-s2-s2s3s4
Alexander polynomial = -3t^5+13t^4-24t^3+24t^2-13t+3

-- L(4)10(4)  (2,2,2)(24-g
s1s1-s2-s2s1s1s3-s2-s2s3
Alexander polynomial = -t^7+5t^6-13t^5+21t^4-21t^3+13t^2-5t+1

-- L(4)10(4)  (2,2,2)(23-h
s1s2-s3-s4-s4-s3-s2-s1-s3-s3s2s4-s3-s3s2
Alexander polynomial = -3t^5+13t^4-24t^3+24t^2-13t+3

-- L(4)10(5)  (2,2)2(2,2)-a
-s1-s2s3s3-s2s1s3s3-s2s3s3-s2
Alexander polynomial = t^7-5t^6+11t^5-15t^4+15t^3-11t^2+5t-1

-- L(4)10(5)  (2,2)2(2,2-b
-s1s2s2-s3s2s2-s1s2s2-s3
Alexander polynomial = t^7-5t^6+11t^5-15t^4+15t^3-11t^2+5t-1

-- L(4)10(5)  (2,2)2(2,3-c
-s1s2s2-s3s2s2s1s2s2-s3s2s2
Alexander polynomial = -t^7+5t^6-11t^5+15t^4-15t^3+11t^2-5t+1

-- L(4)10(5)  (2,2)2(2,2-d
-s1s2s2-s3s4-s3s2s2s1-s2-s2-s3-s4-s3s2
Alexander polynomial = -3t^5+11t^4-18t^3+18t^2-11t+3

-- L(4)10(5)  (2,2)2(2,2-e
-s1s2s2-s1-s3s2s2-s3s2s2
Alexander polynomial = t^7-5t^6+11t^5-15t^4+15t^3-11t^2+5t-1

-- L(4)10(5)  (2,2)2(2,2-f
s1-s2s3s3-s2-s1-s2s3s3-s2s3s3
Alexander polynomial = t^7-5t^6+11t^5-15t^4+15t^3-11t^2+5t-1

-- L(4)10(5)  (2,2)2(2,3-g
-s1s2s2-s3s2s2s1s4-s3-s2-s2-s3-s4-s3s2
Alexander polynomial = -3t^5+11t^4-18t^3+18t^2-11t+3

-- L(4)10(5)  (2,2)2(2,2-h
-s1-s3s2-s3s4-s3s5s4-s3-s2-s2s1-s2-s2-s3-s4-s3s2-s5-s4
Alexander polynomial = -8t^3+24t^2-24t+8

-- L(4)10(6)  (2,2)11(2,2)-a
-s1-s2s3-s4s3s2s1s3s2s4-s3s4s4-s3-s2s4s3
Alexander polynomial = 3t^5-13t^4+24t^3-24t^2+13t-3

-- L(4)10(6)  (2,2)11(23-b
-s1s2-s3s2s1s2s3-s4s3s3-s4s3s2
Alexander polynomial = 3t^5-13t^4+24t^3-24t^2+13t-3

-- L(4)10(6)  (2,2)11(22-c
-s1s2-s3-s3s2s1-s3s2s2-s3s2s2
Alexander polynomial = -t^7+5t^6-13t^5+21t^4-21t^3+13t^2-5t+1

-- L(4)10(6)  (2,2)11(22-d
s1-s2-s3-s3s4-s3-s3-s2-s1-s2s3-s2s4
Alexander polynomial = -3t^5+13t^4-24t^3+24t^2-13t+3

-- L(4)10(6)  (2,2)11(24-e
-s1s2s2-s1-s3-s3s2-s3-s3s2
Alexander polynomial = t^7-5t^6+13t^5-21t^4+21t^3-13t^2+5t-1

-- L(4)10(6)  (2,2)11(22-f
s1-s2s3s3-s2-s1-s2-s2s3-s2-s2s3
Alexander polynomial = t^7-5t^6+13t^5-21t^4+21t^3-13t^2+5t-1

-- L(4)10(6)  (2,2)11(23-g
s1s1-s2s1s1s3-s2-s2s3-s2
Alexander polynomial = -t^7+5t^6-13t^5+21t^4-21t^3+13t^2-5t+1

-- L(4)10(6)  (2,2)11(22-h
s1s2s3-s4-s4s3-s2-s1-s4-s4-s3-s2-s3s4-s3s2-s3
Alexander polynomial = -3t^5+13t^4-24t^3+24t^2-13t+3

-- L(4)10(7)  .(2,2)-a
-s1s2-s3s2-s3s2s1s2-s3-s3s2-s3
Alexander polynomial = t^7-6t^6+16t^5-25t^4+25t^3-16t^2+6t-1

-- L(4)10(7)  .(2,2)-b
s1-s2s3-s2s3-s2s1s3-s2-s2
Alexander polynomial = t^7-6t^6+16t^5-25t^4+25t^3-16t^2+6t-1

-- L(4)10(7)  .(2,2)-c
-s1-s2s3-s2s3-s2s1-s2-s2s3-s2-s2
Alexander polynomial = -t^7+6t^6-16t^5+25t^4-25t^3+16t^2-6t+1

-- L(4)10(7)  .(2,2)-d
s1s2-s3s2-s1s2s3-s4s3-s4s3s2-s4
Alexander polynomial = -3t^5+15t^4-30t^3+30t^2-15t+3

-- L(4)10(7)  .(2,2)-e
s1-s2-s2s1-s2s3-s2s3-s2s3
Alexander polynomial = t^7-6t^6+16t^5-25t^4+25t^3-16t^2+6t-1

-- L(4)10(7)  .(2,2)-f
s1s2-s3s2-s3s2-s1s2-s3-s3s2-s3
Alexander polynomial = t^7-6t^6+16t^5-25t^4+25t^3-16t^2+6t-1

-- L(4)10(7)  .(2,2)-g
-s1s2-s3s2-s1-s1-s3s2-s1-s3
Alexander polynomial = -t^7+6t^6-16t^5+25t^4-25t^3+16t^2-6t+1

-- L(4)10(7)  .(2,2)-h
s1s2s3-s4s3-s2-s1s3-s2s4-s3s4-s3s4-s3s2s3
Alexander polynomial = -3t^5+15t^4-30t^3+30t^2-15t+3

-- L(4)10(8)  .(2,2)-a
-s1-s2s3-s4s3s2s2s1s3s2s3s3s4s3s3-s2s3
Alexander polynomial = -5t^5+17t^4-26t^3+26t^2-17t+5

-- L(4)10(8)  .(2,2)-b
s1-s2s3s3s4-s3-s2-s1-s2s3s4-s3s4s3-s2
Alexander polynomial = -2t^5+14t^4-32t^3+32t^2-14t+2

-- L(4)10(8)  .(2,2)-c
-s1-s2s3-s2-s2s3-s2s1-s2s3s3-s2
Alexander polynomial = t^7-6t^6+16t^5-25t^4+25t^3-16t^2+6t-1

-- L(4)10(8)  .(2,2)-d
-s1s2-s3-s3s2-s1-s3s2s2-s3
Alexander polynomial = t^7-6t^6+16t^5-25t^4+25t^3-16t^2+6t-1

-- L(4)10(8)  .(2,2)-e
s1s1-s2s3-s2s1s1-s2s3-s2
Alexander polynomial = -t^7+5t^6-15t^5+27t^4-27t^3+15t^2-5t+1

-- L(4)10(8)  .(2,2)-f
s1s2-s3-s4-s4-s3-s2-s1-s3s2-s3s4-s3s2-s3
Alexander polynomial = -3t^5+15t^4-30t^3+30t^2-15t+3

-- L(4)10(8)  .(2,2)-g
-s1s2s2-s1-s3s2-s3-s3s2-s3
Alexander polynomial = t^7-6t^6+16t^5-25t^4+25t^3-16t^2+6t-1

-- L(4)10(8)  .(2,2)-h
s1-s2s3s3-s2-s1-s2s3-s2-s2s3-s2
Alexander polynomial = t^7-6t^6+16t^5-25t^4+25t^3-16t^2+6t-1

-- L(4)10(9)-a
s1-s2s3-s2s1s3-s2s1-s2s3
Alexander polynomial = -t^7+7t^6-21t^5+35t^4-35t^3+21t^2-7t+1

-- L(4)10(9)-b
-s1s2-s3s2-s3s2s1s2-s3s2-s3s2
Alexander polynomial = -t^7+7t^6-21t^5+35t^4-35t^3+21t^2-7t+1

-- L(4)10(9)-c
s1s2-s3s2-s3s2-s1s2-s3s2-s3s2
Alexander polynomial = -t^7+7t^6-21t^5+35t^4-35t^3+21t^2-7t+1

-- L(4)10(9)-d
s1-s2s1s3-s2s3-s2s1s3-s2
Alexander polynomial = -t^7+7t^6-21t^5+35t^4-35t^3+21t^2-7t+1

-- L(4)10(9)-e
-s1s2-s1-s3s2-s3s2-s1-s3s2
Alexander polynomial = t^7-7t^6+21t^5-35t^4+35t^3-21t^2+7t-1

-- L(4)10(9)-f
-s1-s2s3-s2s3-s2s1-s2s3-s2s3-s2
Alexander polynomial = t^7-7t^6+21t^5-35t^4+35t^3-21t^2+7t-1

-- L(4)10(9)-g
s1-s2s3-s2s3-s2-s1-s2s3-s2s3-s2
Alexander polynomial = t^7-7t^6+21t^5-35t^4+35t^3-21t^2+7t-1

-- L(4)10(9)-h
-s1s2-s3s2-s1-s3s2-s1s2-s3
Alexander polynomial = t^7-7t^6+21t^5-35t^4+35t^3-21t^2+7t-1

-- L(4)10(10)-a
-s1-s2s3s3s3s3-s2s1-s2-s3-s3-s2
Alexander polynomial = 2t^5-5t^4+5t^3-5t^2+5t-2

-- L(4)10(10)-b
s1s2s2s1-s3s2s2s2s2-s3
Alexander polynomial = -t^7+3t^6-4t^5+4t^4-4t^3+4t^2-3t+1

-- L(4)10(10)-c
-s1-s2-s2s3s2s2s1s2s2-s3s2s2s2s2
Alexander polynomial = -t^7+3t^6-4t^5+4t^4-4t^3+4t^2-3t+1

-- L(4)10(10)-d
s1-s2s3s3-s2-s1s2s3s3s3s3s2
Alexander polynomial = -t^7+3t^6-4t^5+4t^4-4t^3+4t^2-3t+1

-- L(4)10(10)-e
-s1-s2-s3-s3-s2s1-s4s3s3s2-s3s4-s3-s2-s4
Alexander polynomial = -3t^3+9t^2-9t+3

-- L(4)10(10)-f
s1-s2s3s3s4-s3s2-s3-s2-s1s2-s4s3s3s2
Alexander polynomial = 2t^5-5t^4+5t^3-5t^2+5t-2

-- L(4)10(10)-g
s1-s2s3s3-s2-s1s4-s3s2-s3-s2-s4-s3-s3-s2
Alexander polynomial = -3t^3+9t^2-9t+3

-- L(4)10(10)-h
s1s2-s3s4s5-s4-s4-s3-s2-s1s3-s2-s3s4-s3s2s3-s5-s4-s4
Alexander polynomial = 3t^3-9t^2+9t-3

-- L(4)10(11)-a
-s1-s2s3-s4s3s2s1s4-s3s2-s3-s4-s4-s3-s2-s3s4
Alexander polynomial = -5t^3+15t^2-15t+5

-- L(4)10(11)-b
-s1s2-s3s2s1s3-s2s4s3s3-s2s4s3
Alexander polynomial = 2t^5-7t^4+11t^3-11t^2+7t-2

-- L(4)10(11)-c
-s1-s2-s2s3s3s4s3s2s2s1s2s2-s3s2-s4-s3s2
Alexander polynomial = 2t^5-7t^4+11t^3-11t^2+7t-2

-- L(4)10(11)-d
s1s2-s3s4s4-s3-s2-s1s3s2s3-s4s3-s2s4s4s3
Alexander polynomial = 2t^5-7t^4+11t^3-11t^2+7t-2

-- L(4)10(11)-e
-s1-s2-s2-s1-s3-s3-s3s2s2-s3
Alexander polynomial = 2t^5-7t^4+11t^3-11t^2+7t-2

-- L(4)10(11)-f
s1s2s3s3s2-s1-s2-s2-s2s3s3-s2
Alexander polynomial = -t^7+3t^6-6t^5+10t^4-10t^3+6t^2-3t+1

-- L(4)10(11)-g
s1-s2-s3-s3-s2-s2-s2-s1-s2s3s3-s2
Alexander polynomial = 2t^5-7t^4+11t^3-11t^2+7t-2

-- L(4)10(11)-h
s1s2-s3-s4-s4-s4-s4-s3-s2-s1-s3-s2s3s4s3s2-s3
Alexander polynomial = -2t^5+7t^4-11t^3+11t^2-7t+2

-- L(4)10(12)-a
-s1-s2s3s3s3s3-s2s1s2-s3-s3s2
Alexander polynomial = -t^3+3t^2-3t+1

-- L(4)10(12)-b
s1-s2-s2s1-s3s2s2s2s2-s3
Alexander polynomial = -t^3+3t^2-3t+1

-- L(4)10(12)-c
-s1-s2-s2s3-s2-s2s1s2s2-s3s2s2s2s2
Alexander polynomial = -t^3+3t^2-3t+1

-- L(4)10(12)-d
s1s2s3s3s2-s1s2s3s3s3s3s2
Alexander polynomial = t^7-t^6-2t^5+4t^4-4t^3+2t^2+t-1

-- L(4)10(12)-e
-s1s2-s3-s3s2s1-s4s3s3s2-s3s4-s3-s2-s4
Alexander polynomial = -t^3+3t^2-3t+1

-- L(4)10(12)-f
s1-s2s3s3s4-s3s2-s3-s2-s1s2-s4-s3-s3s2
Alexander polynomial = -t^3+3t^2-3t+1

-- L(4)10(12)-g
s1-s2-s3-s3-s2-s1s4-s3s2-s3-s2-s4-s3-s3-s2
Alexander polynomial = 2t^5-3t^4-t^3+t^2+3t-2

-- L(4)10(12)-h
s1s2-s3s4s5-s4-s4-s3-s2-s1s3-s2s3s4s3s2s3-s5-s4-s4
Alexander polynomial = t^3-3t^2+3t-1

-- L(4)10(13) (2,2,2)(2,2-)-a
-s1-s2s3-s4s3s2s1s3s2-s3-s3s4s4s3s3-s2s3
Alexander polynomial = t^5-5t^4+10t^3-10t^2+5t-1

-- L(4)10(13) (2,2,2)(23-b
s1-s2s3s4s3s5s4s3-s2-s1s2s3-s4s3-s5-s4s3s2
Alexander polynomial = -t^5+5t^4-10t^3+10t^2-5t+1

-- L(4)10(13) (2,2,2)(22-c
-s1s2-s3-s3s2s1s2s2-s3-s3-s2-s2
Alexander polynomial = -t^5+5t^4-10t^3+10t^2-5t+1

-- L(4)10(13) (2,2,2)(22-d
-s1s2-s3-s3s2s1-s2-s2-s3-s3-s4s3s2s3s4
Alexander polynomial = t^5-5t^4+10t^3-10t^2+5t-1

-- L(4)10(13) (2,2,2)(24-e
-s1-s2-s2-s3-s3s2s2s1s2-s3-s3s2
Alexander polynomial = -t^5+5t^4-10t^3+10t^2-5t+1

-- L(4)10(13) (2,2,2)(22-f
s1s2-s3-s3s2-s1-s2-s2s3-s4s3-s2-s2s3s4
Alexander polynomial = t^5-5t^4+10t^3-10t^2+5t-1

-- L(4)10(13) (2,2,2)(24-g
s1s1-s2-s2-s1-s1s3-s2-s2s3
Alexander polynomial = -t^5+5t^4-10t^3+10t^2-5t+1

-- L(4)10(13) (2,2,2)(23-h
s1s2s3-s4-s4s3-s2-s1-s3-s3s2s4-s3-s3s2
Alexander polynomial = t^5-5t^4+10t^3-10t^2+5t-1

-- L(4)10(14) (2,2,2-)(2,2)-a
-s1-s2s3-s4s3s2s1-s3s2s3s3s4s4s3s3-s2-s3
Alexander polynomial = 2t^5-8t^4+14t^3-14t^2+8t-2

-- L(4)10(14) (2,2,2-)(3-b
s1-s2-s3s4s3s5s4s3-s2-s1-s2s3-s4s3-s5-s4-s3-s2
Alexander polynomial = -t^5+7t^4-16t^3+16t^2-7t+1

-- L(4)10(14) (2,2,2-)(2-c
-s1s2-s3-s3s2s1s2s2s3s3s2s2
Alexander polynomial = -2t^5+8t^4-14t^3+14t^2-8t+2

-- L(4)10(14) (2,2,2-)(2-d
-s1s2-s3-s3s2s1-s2-s2s3s3-s4-s3s2-s3s4
Alexander polynomial = t^5-7t^4+16t^3-16t^2+7t-1

-- L(4)10(14) (2,2,2-)(4-e
-s1s2s2-s3-s3s2s2s1-s2-s3-s3-s2
Alexander polynomial = t^7-3t^6+7t^5-13t^4+13t^3-7t^2+3t-1

-- L(4)10(14) (2,2,2-)(2-f
s1-s2-s3-s3-s2-s1-s2-s2s3-s4-s3-s2-s2-s3s4
Alexander polynomial = 3t^5-9t^4+12t^3-12t^2+9t-3

-- L(4)10(14) (2,2,2-)(4-g
s1s1s2s2s1s1s3-s2-s2s3
Alexander polynomial = -2t^5+8t^4-14t^3+14t^2-8t+2

-- L(4)10(14) (2,2,2-)(3-h
s1s2-s3-s4-s4-s3-s2-s1-s3-s3s2s4s3s3s2
Alexander polynomial = t^5-7t^4+16t^3-16t^2+7t-1

-- L(4)10(15) (2,2,2-)(2,2-)-a
-s1-s2s3-s4s3s2s1-s3s2-s3-s3s4s4s3s3-s2-s3
Alexander polynomial = -t^5+5t^4-10t^3+10t^2-5t+1

-- L(4)10(15) (2,2,2-)(3-b
s1-s2-s3s4s3s5s4s3-s2-s1s2s3-s4s3-s5-s4-s3s2
Alexander polynomial = t^5-5t^4+10t^3-10t^2+5t-1

-- L(4)10(15) (2,2,2-)(2-c
-s1s2-s3-s3s2s1s2s2s3s3-s2-s2
Alexander polynomial = t^5-5t^4+10t^3-10t^2+5t-1

-- L(4)10(15) (2,2,2-)(2-d
-s1s2-s3-s3s2s1-s2-s2s3s3-s4s3s2s3s4
Alexander polynomial = -t^5+5t^4-10t^3+10t^2-5t+1

-- L(4)10(15) (2,2,2-)(4-e
-s1-s2-s2-s3-s3s2s2s1-s2-s3-s3-s2
Alexander polynomial = t^5-5t^4+10t^3-10t^2+5t-1

-- L(4)10(15) (2,2,2-)(2-f
s1s2-s3-s3s2-s1-s2-s2s3-s4-s3-s2-s2-s3s4
Alexander polynomial = -t^5+5t^4-10t^3+10t^2-5t+1

-- L(4)10(15) (2,2,2-)(4-g
s1s1s2s2-s1-s1s3-s2-s2s3
Alexander polynomial = t^5-5t^4+10t^3-10t^2+5t-1

-- L(4)10(15) (2,2,2-)(3-h
s1s2s3-s4-s4s3-s2-s1-s3-s3s2s4s3s3s2
Alexander polynomial = -t^5+5t^4-10t^3+10t^2-5t+1

-- L(4)10(16) (2,2,2--)(2,2)-a
-s1s2s3s3s2s1s2s2s3s3s2s2
Alexander polynomial = t^7-t^6-3t^5+7t^4-7t^3+3t^2+t-1

-- L(4)10(16) (2,2,2--)2-b
-s1s2s3s3s2s1-s2-s2s3s3-s4-s3s2-s3s4
Alexander polynomial = t^5+t^4-8t^3+8t^2-t-1

-- L(4)10(16) (2,2,2--)4-c
-s1-s2-s3-s4-s3s2s1-s3s2s3s3s4s4s3s3-s2-s3
Alexander polynomial = 2t^3-6t^2+6t-2

-- L(4)10(16) (2,2,2--)3-d
s1-s2-s3s4-s3s5s4s3-s2-s1-s2s3-s4-s3-s5-s4-s3-s2
Alexander polynomial = t^5-3t^4+4t^3-4t^2+3t-1

-- L(4)10(16) (2,2,2--)2-e
s1s1s2s2s1s1-s3-s2-s2-s3
Alexander polynomial = -2t^3+6t^2-6t+2

-- L(4)10(16) (2,2,2--)3-f
s1s2-s3-s4-s4-s3-s2-s1-s3-s3-s2s4s3s3-s2
Alexander polynomial = -t^5+3t^4-4t^3+4t^2-3t+1

-- L(4)10(16) (2,2,2--)2-g
-s1s2s2-s3-s3s2s2s1-s2s3s3-s2
Alexander polynomial = -2t^3+6t^2-6t+2

-- L(4)10(16) (2,2,2--)2-h
s1-s2-s3-s3-s2-s1-s2-s2s3-s4-s3s2s2-s3s4
Alexander polynomial = -t^5+3t^4-4t^3+4t^2-3t+1

-- L(4)10(17) (2,2,2)-(2,2)-a
-s1-s2s3-s4s3s2s1s3s2-s3-s3s4s4-s3-s3-s2s3
Alexander polynomial = 2t^5-4t^4+2t^3-2t^2+4t-2

-- L(4)10(17) (2,2,2)-(3-b
s1s2s3s4s3s5s4s3s2-s1s2s3-s4s3-s5-s4s3s2
Alexander polynomial = t^5+t^4-8t^3+8t^2-t-1

-- L(4)10(17) (2,2,2)-(2-c
-s1s2-s3-s3s2s1-s2-s2-s3-s3-s2-s2
Alexander polynomial = t^7-3t^6+3t^5-t^4+t^3-3t^2+3t-1

-- L(4)10(17) (2,2,2)-(2-d
-s1-s2-s3-s3-s4s3s2s2s1s3s2s4-s3-s3s2
Alexander polynomial = t^5-3t^4+4t^3-4t^2+3t-1

-- L(4)10(17) (2,2,2)-(2-e
-s1-s2-s2-s3-s3-s2-s2s1s2-s3-s3s2
Alexander polynomial = t^7-3t^6+3t^5-t^4+t^3-3t^2+3t-1

-- L(4)10(17) (2,2,2)-(2-f
-s1-s2s3-s4-s3-s3s2s2s1s2-s3-s3s2s4s3
Alexander polynomial = t^5-3t^4+4t^3-4t^2+3t-1

-- L(4)10(17) (2,2,2)-(3-g
-s1-s1-s2-s2-s1-s1s3-s2-s2s3
Alexander polynomial = t^7-3t^6+3t^5-t^4+t^3-3t^2+3t-1

-- L(4)10(17) (2,2,2)-(3-h
s1s2s3-s4s3-s2-s1-s3-s3s2s4s4-s3-s3s2
Alexander polynomial = t^5-3t^4+4t^3-4t^2+3t-1

-- L(4)10(18) .(2,2-)-a
-s1s2-s3s2-s3s2s1s2s3s3s2-s3
Alexander polynomial = t^5-5t^4+10t^3-10t^2+5t-1

-- L(4)10(18) .(2,2-)-b
-s1-s2-s2-s1-s2s3-s2s3-s2s3
Alexander polynomial = -t^7+4t^6-6t^5+5t^4-5t^3+6t^2-4t+1

-- L(4)10(18) .(2,2-)-c
-s1-s2s3-s2s3-s2s1s2s2s3-s2-s2
Alexander polynomial = -t^5+5t^4-10t^3+10t^2-5t+1

-- L(4)10(18) .(2,2-)-d
s1-s2-s3-s2-s1s2s3-s4s3-s4s3s2-s4
Alexander polynomial = t^5-5t^4+10t^3-10t^2+5t-1

-- L(4)10(18) .(2,2-)-e
s1s2s2s1-s2s3-s2s3-s2s3
Alexander polynomial = t^5-5t^4+10t^3-10t^2+5t-1

-- L(4)10(18) .(2,2-)-f
s1s2-s3s2-s3s2-s1-s2-s3-s3-s2-s3
Alexander polynomial = -t^7+4t^6-6t^5+5t^4-5t^3+6t^2-4t+1

-- L(4)10(18) .(2,2-)-g
-s1s2-s3s2s1s1-s3s2-s1-s3
Alexander polynomial = -t^5+5t^4-10t^3+10t^2-5t+1

-- L(4)10(18) .(2,2-)-h
s1s2-s3-s4-s3-s2-s1s3-s2s4-s3s4-s3s4-s3s2s3
Alexander polynomial = t^5-5t^4+10t^3-10t^2+5t-1

-- L(4)10(19) .(2,2-)-a
-s1-s2s3-s4s3s2s2s1s3s2s3s3s4-s3-s3-s2s3
Alexander polynomial = 2t^5-8t^4+14t^3-14t^2+8t-2

-- L(4)10(19) .(2,2-)-b
s1-s2s3s3s4-s3-s2-s1s2s3s4-s3s4s3s2
Alexander polynomial = 2t^5-8t^4+14t^3-14t^2+8t-2

-- L(4)10(19) .(2,2-)-c
-s1-s2s3-s2-s2s3-s2s1-s2-s3-s3-s2
Alexander polynomial = 2t^5-8t^4+14t^3-14t^2+8t-2

-- L(4)10(19) .(2,2-)-d
s1s2s2s1-s3s2-s3-s3s2-s3
Alexander polynomial = -t^7+4t^6-8t^5+11t^4-11t^3+8t^2-4t+1

-- L(4)10(19) .(2,2-)-e
s1s1-s2s3-s2-s1-s1-s2s3-s2
Alexander polynomial = -t^5+7t^4-16t^3+16t^2-7t+1

-- L(4)10(19) .(2,2-)-f
s1s2s3-s4-s4s3-s2-s1-s3s2-s3s4-s3s2-s3
Alexander polynomial = t^5-7t^4+16t^3-16t^2+7t-1

-- L(4)10(19) .(2,2-)-g
-s1-s2-s2-s1-s3s2-s3-s3s2-s3
Alexander polynomial = 2t^5-8t^4+14t^3-14t^2+8t-2

-- L(4)10(19) .(2,2-)-h
s1s2s3s3s2-s1-s2s3-s2-s2s3-s2
Alexander polynomial = -t^7+4t^6-8t^5+11t^4-11t^3+8t^2-4t+1

-- L(4)10(20) .-(2,2)-a
-s1-s2s3-s2-s2s3-s2s1s2-s3-s3s2
Alexander polynomial = 0

-- L(4)10(20) .-(2,2)-b
-s1-s2s3-s4s3s2s2s1s3s2-s3-s3s4-s3-s3-s2s3
Alexander polynomial = t^5-t^4-2t^3+2t^2+t-1

-- L(4)10(20) .-(2,2)-c
s1-s2-s2s1-s3s2-s3-s3s2-s3
Alexander polynomial = 0

-- L(4)10(20) .-(2,2)-d
s1s2s3s3s4-s3s2-s1s2s3s4-s3s4s3s2
Alexander polynomial = -2t^5+2t^4+4t^3-4t^2-2t+2

-- L(4)10(20) .-(2,2)-e
s1s2-s3-s3s2s1-s3-s2-s2-s3
Alexander polynomial = 0

-- L(4)10(20) .-(2,2)-f
-s1-s1-s2s3-s2-s1-s1-s2s3-s2
Alexander polynomial = t^7-3t^6+t^5+5t^4-5t^3-t^2+3t-1

-- L(4)10(20) .-(2,2)-g
s1s2-s3-s3s2-s1-s2s3-s2-s2s3-s2
Alexander polynomial = 0

-- L(4)10(20) .-(2,2)-h
s1s2s3-s4s3-s2-s1-s3s2-s3s4s4-s3s2-s3
Alexander polynomial = t^5-t^4-2t^3+2t^2+t-1

-- L(4)10(21)-a
s1s2-s3s2-s3s2-s1-s2s3-s2s3-s2
Alexander polynomial = 0

-- L(4)10(21)-b
s1-s2s1-s3s2-s3s2s1-s3-s2
Alexander polynomial = 0

-- L(4)10(21)-c
-s1s2-s1s2-s1s3-s2s3-s2s3
Alexander polynomial = 0

-- L(4)10(21)-d
-s1-s2s3-s2s3-s2s1s2-s3s2-s3s2
Alexander polynomial = 0

-- L(4)10(21)-e
s1s2-s3s2-s3s2-s1-s2s3-s2s3-s2
Alexander polynomial = 0

-- L(4)10(21)-f
s1-s2s1-s2s1-s3s2-s3s2-s3
Alexander polynomial = 0

-- L(4)10(21)-g
-s1s2-s1s3-s2s3-s2-s1s3s2
Alexander polynomial = 0

-- L(4)10(21)-h
-s1s2-s3s2-s3s2s1-s2s3-s2s3-s2
Alexander polynomial = 0


back to braid results    back to braid page